Crash testing machine learning force fields for molecules, materials, and interfaces: model analysis in the TEA Challenge 2023 - Poltavsky, Igor; Charkin-Gorbulin, Anton; Puleva, Mirela; Fonseca, Grégory; Batatia, Ilyes; Browning, Nicholas J.; Chmiela, Stefan; Cui, Mengnan; Frank, J. Thorben; Heinen, Stefan; Huang, Bing; Käser, Silvan; et al. (Chemical Science, 2025)
Atomistic simulations are routinely employed in academia and industry to study the behavior of molecules, materials, and their interfaces. Central to these simulations are force fields (FFs), whose development is challenged by intricate interatomic interactions at different spatio-temporal scales and the vast expanse of chemical space. Machine learning (ML) FFs, trained on quantum-mechanical energies and forces, have shown the capacity to achieve sub-kcal (mol−1 Å−1) accuracy while maintaining computational efficiency. The TEA Challenge 2023 rigorously evaluated commonly used MLFFs across diverse applications, highlighting their strengths and weaknesses. Participants trained their models using provided datasets, and the results were systematically analyzed to assess the ability of MLFFs to reproduce potential energy surfaces, handle incomplete reference data, manage multi-component systems, and model complex periodic structures. This publication describes the datasets, outlines the proposed challenges, and presents a detailed analysis of the accuracy, stability, and efficiency of the MACE, SO3krates, sGDML, SOAP/GAP, and FCHL19* architectures in molecular dynamics simulations. The models represent the MLFF developers who participated in the TEA Challenge 2023. All results presented correspond to the state of the ML architectures as of October 2023. A comprehensive analysis of the molecular dynamics results obtained with different MLFFs will be presented in the second part of this manuscrip
CRIS-Team Scopus Importer:2025-02-14